2023
DOI: 10.3390/cells12091247
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue-Derived Stem Cell Extracellular Vesicles Suppress Glioblastoma Proliferation, Invasiveness and Angiogenesis

Abstract: Extracellular vesicles (EVs) are attractive anticancer drug delivery candidates as they confer several fundamental properties, such as low immunogenicity and the ability to cross biological barriers. Mesenchymal stem cells (MSCs) are convenient producers for high EV yields, and patient-derived adipose tissue MSC-EVs could serve as personalised carriers. However, MSC-EV applications raise critical concerns as their natural cargo can affect tumour progression in both inducing and suppressing ways. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The second phase consisted of questions about CAM methodology, results, discussion, and conclusions. The articles were classified according to the score obtained: low quality (score 0-5), medium quality (score 6-15), and high quality (score [16][17][18][19][20]. Following this quality study, 6 articles were excluded (Figure 1), and 74 articles were included and are analyzed in Tables 1-5.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second phase consisted of questions about CAM methodology, results, discussion, and conclusions. The articles were classified according to the score obtained: low quality (score 0-5), medium quality (score 6-15), and high quality (score [16][17][18][19][20]. Following this quality study, 6 articles were excluded (Figure 1), and 74 articles were included and are analyzed in Tables 1-5.…”
Section: Data Extractionmentioning
confidence: 99%
“…In half of the studies analyzed (55%), tumor establishment was established with Matrigel, although culture medium (18%) and PBS (9%) were also used. However, other matrices are also used to establish tumor growth, as in the case of Gečys et al (2023), who used rat tail collagen as the matrix for cell inoculation [16], or Yart et al (2022), who used Geltrex [22]. On the other hand, it should be noted that only 9% of the studies used a silicone ring in the CAM to infiltrate the tumor cells into the CAM and facilitate its establishment at a fixed point, preventing its spread through the CAM (Figure 4D).…”
Section: Establishment and Tumor Formation In The Cam From Cell Lines...mentioning
confidence: 99%
“…It has been demonstrated that CCL5 secreted by ADMSCs can induce PD-L1 expression in breast cancer cells ( 61 ). Exosomes derived from ADMSCs reduce glioblastoma proliferation and significantly down-regulate the invasion-related genes ITGα5 and ITGβ3, as well as the angiogenesis induction gene KDR ( 62 ).…”
Section: Regulatory Effects Of Mscs From Different Sources On Tumor C...mentioning
confidence: 99%
“…ADSCs have the ability to differentiate into multiple cell types, including adipocytes, osteoblasts, chondrocytes, and myocytes [ 4 ]. In addition, ADSCs secrete various growth factors and cytokines that promote tissue repair and regeneration [ 5 , 6 ]. Exosomes are small membrane-bound vesicles that can transport proteins, nucleic acids, and other molecules between cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ADSCs and ADSC-Ex have been investigated for their therapeutic potential in various diseases and conditions, including wound healing, tissue regeneration, autoimmune diseases, and neurological disorders [6,11]. In preclinical studies, ADSCs and adipose-derived mesenchymal stem cell extracellular vesicles (ADSC-EVs) have shown promising results in improving tissue function and reducing inflammation in animal models of these diseases [12].…”
Section: Introductionmentioning
confidence: 99%